Gravitational waves discovery, intellectual property and technology transfer. (December 2017) - Trainer, Matthew
Abstract: Gravitational waves were discovered in the USA on the 14th September 2015. The worldwide media have presented this as a significant achievement of scientific discovery. Detection of the waves was due to the development of accurate and sensitive scientific measurement instrumentation by an international collaboration of scientists. However, patents on the detection of gravitational waves are few. Technology transfer of intellectual property by science groups associated with gravitational waves research has been identified and has the potential of yielding important spinoffs now and in future years.